Respon Masyarakat Lokal Terhadap Aktivitas Hiburan Malam Di Legian, Kuta - Panjaitan, Juliyanti; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA, 2018)
Night entertainments become a special attraction for tourists to fulfill their holidays in Bali with just listening to the music’s or enjoying drinks provided in bars, discotheque/cafes. By these facilities, Bali become a magnet of both domestic and foreign tourists. The types of data used are qualitative and quantitative data, while the data sources used are primary data and secondary data. The data collecting is done with the observation field, in-depth interview, and questionnaires. Then the data were analyzed using descriptive qualitative with the record and explain the results cleary based on the formulation of a problem that has been determined, as well as questionnaires are analyzed using quantitative data as data supporters of the research.   The results of this research explains that there are several different types of activities that can be done in place of evening entertainment, including dancing, enjoy music, and enjoy drinks and meals are offered in the café/restaurant. Then from the results of the questionnaire obtained the results that the response of local communities included in the stages of Apathy, which previously accepted as tourism sector economic growth but this time its presence was felt not to mention everything. People living in the surroundings feel uncomfortable and insecure due to the activity of the night until the early hours Keywords : Response of Local People, Night Entertainment, Legian Kuta